2017
DOI: 10.1556/2060.104.2017.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of testosterone on mean arterial pressure: A physiological study in male and female normotensive WKY and hypertensive SHR rats

Abstract: Introduction Testosterone plays an important role in the blood pressure regulation. However, information with regard to the effect of this hormone on blood pressure in normotensive and hypertensive conditions is limited. Therefore, in this study, the relationship between plasma testosterone level and mean arterial pressure (MAP) was investigated under these conditions. Methods Normotensive Wistar-Kyoto (WKY) and hypertensive Spontaneous Hypertensive (SHR) male and female rats were gonadectomized with female ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It is worth noting that there are inconsistent reports on the effect of ovariectomy on blood pressure. Loh SY et al found that the mean arterial pressure of 8-week-old female SHR decreased after gonadectomy (Loh et al 2017). Masubuchi et al also showed that gonadectomy may affect blood pressure in adult female rats (Masubuchi et al1982).…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting that there are inconsistent reports on the effect of ovariectomy on blood pressure. Loh SY et al found that the mean arterial pressure of 8-week-old female SHR decreased after gonadectomy (Loh et al 2017). Masubuchi et al also showed that gonadectomy may affect blood pressure in adult female rats (Masubuchi et al1982).…”
Section: Discussionmentioning
confidence: 98%
“…However, most current studies have focused on the relationship between serum total testosterone (TT) and blood pressure (BP) regulation in male patients. 10 , 11 Studies on the role of bioavailable testosterone (BioT) in postmenopausal hypertensive women with LVH have rarely been reported. By analyzing the relationship between androgen and LVH in postmenopausal hypertensive women, this study aims to provide a new predictor and theoretical basis for target organ damage in postmenopausal hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Again, since no significant improvement of cardiac function were observed after testosterone supplementation, we considered the increment of SBP after supplementation of testosterone may be also depended on its efficacy on volume and strength of peripheral skeletal muscle. This is not surprising since the contraction of peripheral skeletal muscle may serve as a secondary pump to maintain the BP, particularly in the elderly (36,37). Furthermore, results our meta-analysis did not support that testosterone supplementation in CHF patients was associated with significantly improved prognosis.…”
Section: Discussionmentioning
confidence: 58%